2016
DOI: 10.3390/ijms17091379
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Antioxidants and Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is one of the most important chronic liver diseases worldwide and has garnered increasing attention in recent decades. NAFLD is characterized by a wide range of liver changes, from simple steatosis to nonalcoholic steatohepatitis, cirrhosis, and hepatocellular carcinoma. The blurred pathogenesis of NAFLD is very complicated and involves lipid accumulation, insulin resistance, inflammation, and fibrogenesis. NAFLD is closely associated with complications such as obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 141 publications
1
56
0
1
Order By: Relevance
“…[110] AX is a xanthophyll carotenoid that is recognized as a novel antioxidant preventing cardiovascular and liver diseases. [112] We previously found that AX decreases fat accumulation and peroxidation in diet-induced NASH mice and primary hepatocytes. [111] We also reported that lycopene ameliorates diet-induced fatty liver and hepatic inflammation in the mice fed with HFD or CL diet by promoting M2-dominant polarization in adipose tissue, suggesting its potential role in the treatment of liver diseases.…”
Section: Micronutrient Antioxidantsmentioning
confidence: 94%
“…[110] AX is a xanthophyll carotenoid that is recognized as a novel antioxidant preventing cardiovascular and liver diseases. [112] We previously found that AX decreases fat accumulation and peroxidation in diet-induced NASH mice and primary hepatocytes. [111] We also reported that lycopene ameliorates diet-induced fatty liver and hepatic inflammation in the mice fed with HFD or CL diet by promoting M2-dominant polarization in adipose tissue, suggesting its potential role in the treatment of liver diseases.…”
Section: Micronutrient Antioxidantsmentioning
confidence: 94%
“…As with vitamin E, astaxanthin significantly reduced the levels of the oxidative stress marker thiobarbituric acid reactive substances (TBARS) in the livers of mice with NASH [14]. Vitamin E has been used as a therapeutic component for NAFLD through its inhibition of reactive oxygen species production [13]. Our results suggested that vitamin E effectively reduced ER stress and improved EIF2 protein translation.…”
Section: Discussionmentioning
confidence: 86%
“…A meta-analysis of randomized controlled trials concluded that supplementation with astaxanthin had a slight plasma glucose-lowering effect [10]. Recently, astaxanthin’s protective effect on liver function has been attracting attention [9,11,12,13]. We have previously shown that astaxanthin ameliorated hepatic steatosis in both ob/ob and high-fat-diet-induced obese mice [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been informed that EGC enriched LSE as an anti-inflammatory agent in Lipopolysaccharides-stimulated HepG2 cells and mice [25]. Recent evidences have focused on the control for NAFLD pathogenesis using micronutrient antioxidants and/or dietary components, such as vitamins and polyphenols [41][42][43]. In the literature, polyphenols are a heterogeneous class of plant-derived compounds, with some confirmed hepatoprotective effects [44].…”
Section: Discussionmentioning
confidence: 99%